Dilemma in the preservation practice of traditional Malay houses - Abdul Latip, Nurul Syala; Sulaiman, Norhafizatullakmar; Kamaruddin, Zumahiran; Mansor, Mazlina; Harun, Nor Zalina (2014)
Traditional Malay houses in Malaysia are examples of the rich Malay (the largest community in Malaysia) cultural heritages. However, developments that are growing rapidly in many areas in Malaysia had replaced traditional village areas with new developments. These actions diminished with them many traditional Malay houses. Nowadays, preservation of these houses becomes crucial to protect the cultural heritage of Malaysia and the culture of the Malays that lie within the architecture of these houses. The Malay cultures are manifested in the form, spatial layout and the details of these houses. The research aims to establish the categories of preservation practice in traditional Malay house and the factor which influence it. Qualitative method was employed with in-depth interview technique through case study. Kuala Kangsar was chosen as the case study area. It was named as the heritage zone for the state of Perak. This is due to the rich cultural heritage contents in the area that includes traditional Malay houses. The research discussed the findings of the initial study towards preservation practices on traditional Malay houses in Kuala Kangsar. The findings revealed that lack of awareness among the users on the cultural value of the traditional houses, changes of building owners and changes on the daily needs of the users are among the reasons why the traditional houses were not well preserved.